2021
DOI: 10.1101/2021.02.02.21251038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DermoExpert: Skin lesion classification using a hybrid convolutional neural network through segmentation, transfer learning, and augmentation

Abstract: Although automated Skin Lesion Classification (SLC) is a crucial integral step in computer-aided diagnosis, it remains a challenging task due to inconsistency in texture, color, indistinguishable boundaries, and shapes. In this article, we propose an automatic and robust framework for the dermoscopic SLC named Dermoscopic Expert (DermoExpert). The DermoExpert consists of a preprocessing, a hybrid Convolutional Neural Network (hybrid-CNN), and transfer learning. The proposed hybrid-CNN classifier consists of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Those features can be utilized to develop a sensitive Computer-aided Diagnosis (CAD) tool to detect COVID- Pneumonia and be considered as a screening tool [14] . Currently, deep Convolutional Neural Networks (CNNs) allow for building an end-to-end model, without the need for manual feature extraction [15] , [16] , which have demonstrated tremendous success in many domains of medical imaging, such as arrhythmia detection [17] , [18] , [19] , skin lesion segmentation and classification [20] , [21] , [22] , [23] , [24] , breast cancer detection [25] , [26] , [27] , brain disease classification [28] , pneumonia detection from CXR images [29] , fundus image segmentation [30] , [31] , minimally invasive surgery [32] and lung segmentation [33] . Several deep CNN-based methods have been published to detect COVID-19 from CXR and CT images.…”
Section: Introductionmentioning
confidence: 99%
“…Those features can be utilized to develop a sensitive Computer-aided Diagnosis (CAD) tool to detect COVID- Pneumonia and be considered as a screening tool [14] . Currently, deep Convolutional Neural Networks (CNNs) allow for building an end-to-end model, without the need for manual feature extraction [15] , [16] , which have demonstrated tremendous success in many domains of medical imaging, such as arrhythmia detection [17] , [18] , [19] , skin lesion segmentation and classification [20] , [21] , [22] , [23] , [24] , breast cancer detection [25] , [26] , [27] , brain disease classification [28] , pneumonia detection from CXR images [29] , fundus image segmentation [30] , [31] , minimally invasive surgery [32] and lung segmentation [33] . Several deep CNN-based methods have been published to detect COVID-19 from CXR and CT images.…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies used to improve the performance in classification of medical signals or images is to use several models together 32–35 or the transfer learning 36,37 . It is also observed that this approach is used in the classification of brain tumors 26–28 .…”
Section: Introductionmentioning
confidence: 99%
“…CNNs are also becoming very popular in medical image analysis [7] and many decision support systems have been developed, for example, for automatic reporting of medical exams [8] and analysis of retinal fundus images [9]. Moreover, CNNs were also successfully employed in skin lesion analysis to classify and segment nevi and melanomas [10,11,12,13,14]. Melanoma is an aggressive form of cancer, triggered by an uncontrolled proliferation of melanocytes, pigment-producing cells of neuroectodermal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only a small fraction of the ISIC images was also labelled at the pixel-level, since the high cost of image tagging by medical experts made the collection of large sets of segmentation label maps very difficult. However, lesion segmentation also proved very useful in improving the classification accuracy [13,14], as the lesion boundaries are also used by dermatologists for their diagnosis. To this end, a weakly-supervised approach, inspired by [17], was employed to automatically extract segmentation supervisions for approximately 43,000 ISIC images.…”
Section: Introductionmentioning
confidence: 99%